The Stigmatized Hero? A Review of UK Opinion Polls and Surveys on Perceptions of British Veterans in UK Society - Rita Phillips (Journal of Veterans Studies, 2020)
Findings from representative opinion polls and surveys provide information on pertinent perceptions of veterans in British society. The present project compares these findings and contrast publicly pertinent perceptions of veterans with factually correct information. This allows researchers to determine erroneous and stereotyped perceptions of veterans that may be held by members of the British society. The present project reviewed 41 veteran-related question-items from 11 surveys/polls and grouped these question items into the categories 1) employment situation, 2) housing situation, 3) skills and experiences, 4) physical/psychological well-being, and, 5) addictions and antisocial behaviour. The comparison with factually correct information indicates that the majority of the respondents held a set of negative and erroneous stereotypes against veterans. As negative and erroneous stereotypes may hinder a successful transition into civilian society, future research should explore how these stereotypes may form.